Practice conditions: How do they influence motor learning in golf? - Keogh, J.; Hume, P. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study reviewed the literature for the effect that various practice conditions have on motor learning in golf. All eligible studies had to use outcome measures of direct (ball displacement, shot accuracy) or indirect (clubhead velocity, clubface angle) golf performance. Results of the six eligible studies suggests that a distributed practice approach involving multiple sessions per week of block, errorless practice may be best for improving putting accuracy of novice golfers. Random (variable) practice may however lead to greater putting performance improvements in skilled golfers. Coaches and golfers should therefore consider the way they structure their practice sessions in order to better facilitate improvements in golf performance.